MAHMOOD KASHKARI - FOUNDER OF AREAL LINGUISTICS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Mahmoud Kashkari’s «Divani lugat-At-Turkish Dictionary» identifies the author as the founder of areal linguistics. Here it is necessary to focus on М. Kashkari’s multilingualism and the map of the world he created. Although the dictionary has been studied in various ways in the science of philology, it indirectly tells about the map of the world. Mainly due to the toponyms included in the map, the dictionary has been brought to a new level. It reflects the geographical boundaries of the Turkic tribes, the peculiarities of language contacts, the processes of defining the boundaries of various branches and areas of science.
Keywords: area, toponyms, geographical boundaries, world map, Turkology, branches of science